2018
DOI: 10.1002/2211-5463.12395
|View full text |Cite
|
Sign up to set email alerts
|

The TNF‐α‐induced expression of miR‐130b protects cervical cancer cells from the cytotoxicity of TNF‐α

Abstract: Tumour necrosis factor alpha (TNF‐α) is a multifunctional cytokine and has the capacity both to promote cell growth and to kill tumour cells by inducing cell apoptosis. However, many tumour cells develop resistance to the toxic effects of TNF‐α. Thus, understanding the mechanism underlying the resistance of tumours to TNF‐α toxicity and finding ways to overcome this resistance are urgently needed. In this study, we discovered that two cervical cancer cell lines, Hela and Siha, showed null responses to TNF‐α cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Therefore, imbalance or disturbance in one part can promote the formation of tumors ( Jouhi et al, 2014 ). Mutated TNF-α can directly lead to cell canceration ( Yang et al, 2018 ). Meanwhile, IL-6, IL-8, IL-1β, and other inflammatory cytokines can promote tumor proliferation and the development of cervical cancer ( Schäfer et al, 2013 ; Liu et al, 2020 ).…”
Section: The Driving Effects Of Microbiome On Cervical Cancermentioning
confidence: 99%
“…Therefore, imbalance or disturbance in one part can promote the formation of tumors ( Jouhi et al, 2014 ). Mutated TNF-α can directly lead to cell canceration ( Yang et al, 2018 ). Meanwhile, IL-6, IL-8, IL-1β, and other inflammatory cytokines can promote tumor proliferation and the development of cervical cancer ( Schäfer et al, 2013 ; Liu et al, 2020 ).…”
Section: The Driving Effects Of Microbiome On Cervical Cancermentioning
confidence: 99%
“…10 In addition, TNF-a could induce nuclear factor kB (NF-kB), C-fos, and C-Jun expression and regulate the immunoreaction, which is a broad spectrum of pro-inflammatory cytokines. 11 Previous studies suggested that TNF-a was overexpressed in the lung and nasal mucosa, which played an important role in airway inflammatory responses. 12 However, at present, TNF-a roles in Asian patients with CRSwNP have not been illuminated.…”
Section: Introductionmentioning
confidence: 99%
“…IL-2 has been used for the treatment of many different kinds of cancer, and Lagunas-Cruz et al reported that IL-2 decreases cervical cancer cell proliferation through the transient arrest of the G1 phase [ 31 ]. TNF‑α, a cytokine naturally synthesized by the macrophages that directly leads to the death of cancer cells [ 32 ]. Meanwhile, the inflammatory cytokines, such as IL-6, IL-8, and IL-1β can promote tumor proliferation and the occurrence and development of cervical cancer [ 28 ].…”
Section: Discussionmentioning
confidence: 99%